The influence of shift work on the psychomotor capabilities of emergency medicine residents. Issue 6 (6th December 2021) - Zahraie, Mehrnoosh Aligholi; Alaedini, Farshid; Payandemehr, Pooya; Saadat, Soheil; Sotoodehnia, Mehran; Bahreini, Maryam
Abstract: Objective: Shift work affects health status of healthcare providers and patients. We assessed the effect of shift work on psychomotor activities of emergency medicine residents of 3 university hospitals. Methods: The participants were enrolled to perform selected psychomotor tests via the Vienna test system (VTS) after written consent. They passed 4 episodes of test performance before and after 2 consecutive day and night clinical shifts of 12 hours. The status of general health, circadian rhythm, sleepiness, smoking habits, and the scores of the cognition test (COG), the determination test (DT), and the visual pursuit test of emergency medicine residents were compared before and after morning and night shifts. Results: Overall, 23 residents (34.8% were male) performed tests. The mean (SD) age was 35.7 + 8.5 years. The mean general health and circadian scores before and after day/night shifts were not different. The Stanford sleepiness scale showed higher scores after night shifts. In the cognition test, the sum of correct rejections was higher after day shifts. Moreover, in the DT results, correct responses were more prevalent, the omitted responses were fewer accompanied by better median reaction time after day shifts. The sum of correct rejections of the COG test showed difference in terms of improved results in night tests compared to day‐shift tests. The mean reaction time of the DT showed significant difference with shorter reaction time in night‐shift tests. The visual pursuit test results were not different between day and night shifts. Conclusions: Sleepiness was higher after night shifts. The results of selected psychomotor tests showed that the psychomotor function of the residents was not delayed or worse after night shifts in comparison to the day shifts.